Experimental and modelling study of fatigue crack initiation in an aluminium beam with a hole under 4-point bending. (1st May 2018) - Ye, Wenye; Efthymiadis, Panos; Pinna, Christophe; Ma, Anxin; Shollock, Barbara; Dashwood, Richard
Abstract: Slip band formation and crack initiation during cyclic fatigue were investigated by in-situ experiments and non-local CPFEM simulations systematically. Experimental techniques including EBSD, digital image correlation (DIC) and SEM have been used to obtain consistent grain orientations, local strains, as well as the locations where slip bands and micro-cracks form on the sample surface. The realistic microstructure based on the EBSD map has been generated and used for finite element modelling. An advanced non-local crystal plasticity model, which considers the isotropic and kinematic hardening of the plastic strain gradient, has been adopted. The simulation results match well the corresponding experimental results. It was found that total strain and averaged slip on all slip systems, combined with accumulated slip on specific slip planes help predict the location and orientation of slip bands and micro-crack initiation correctly. Furthermore, a fatigue indicating parameter based on competition between maximum slip and the total slip has been proposed to reproduce the experimental observations.